Notes on the family Bromeliaceae in the Valley of Mexico - Espejo Serna, Adolfo; López-Ferrari, Ana Rosa (Instituto de Ecología, A.C., 2004)
Some corrections and nomenclatural changes and one addition to the Bromeliaceae in the Flora fanerogámica del Valle de México are presented.